THEOLOGICAL KNOWLEDGE IN ISLAMIC MYSTICISM AND GNOSTICISM - Fereshteh Jafari (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2020)
In this paper, the similarities between the Gnostic and Islamic mystic beliefs about “Knowledge” (Ma‘refat) will be considered. The aim is to answer the question of whether they share a common view of divine knowledge. For this purpose, first Gnosticism and its ideas will be clarified. Second, a brief history of Islamic Mysticism will be presented. Then, in light of the evolution path of such beliefs, the main principles of both cults about the Gnosis and Mysticism will be reconsidered. The methodology of this study is based on a comparative study, by analyzing Islamic mystical books and Gnostic texts. Through the study of mystical books, the traditions and beliefs of the early mystics, in this case, are stated, and some examples from the Gnostic books about the Gnosis and mystical knowledge are mentioned. The comparative study of these two religions revealed that they have many similarities in points of view to “knowledge”. Similarities between Islamic mysticism and Gnosticism are so much that some believe that the theory of divine knowledge in the minds of Muslim Sufis originates from Gnostic ideas. But this claim cannot be completely true and the Gnostic beliefs have only had influences on it.